The role of the sound’s qualities in the auditory imagery - Vázquez-Sánchez, Rubén (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Sound mental images are the product of copies or reconstructions of past perceptual experiences or the product of anticipation of possible future experiences, but in the absence of appropriate external stimuli. However, in music, how these interact with external visual perceptions in the recreation or generation of auditory mental images is not known for certain. Throughout this literature review, we will attempt to discern how each of the qualities of sound infers or elicits a response in thought processes and provides the semantic basis for musical language.